Design and Implementation of the Mount Ciremai Basecamp Website as a Climbing Information Media in Linggasana Village - Lesmana, Surya; Saputra, Andika Bagus; Baihaqi, Egi Ahmad; Syakur, Muhamad Zidan; Suhendi, Suhendi (Al-Makki Publisher, 2025)
Mount Ciremai is the highest mountain in West Java Province which is the main destination for climbing and natural tourism. One of the official climbing trails of Mount Ciremai is in Linggasana Village which has a basecamp as a center for climbing services and information. However, the delivery of climbing information at the Linggasana Village basecamp is still carried out conventionally, so that information is difficult for prospective climbers to access widely and quickly. This research aims to design and implement a Mount Ciremai Basecamp website in Linggasana Village as an integrated and easily accessible climbing information medium. The research method used is the Waterfall method which includes the stages of needs analysis, system design, implementation, and testing. The website is developed using web-based technology with an integrated database. The results of the study show that the website built is able to present climbing information effectively and help climbers in obtaining accurate information before climbing. The study also reveals that the website facilitates faster information updates, broader information coverage, and better documentation. The implications of this research indicate that the use of web-based information systems can enhance service quality, transparency, and climber preparedness, while also supporting safer and more sustainable climbing management. In conclusion, the implementation of the website provides an effective solution to overcome the limitations of conventional information delivery and contributes both practically and theoretically to the development of information systems in natural tourism management.